KORELASI AKTIVITAS ORGANISASI TERHADAP CAPAIAN AKADEMIK MAHASISWA "KULIAH-RAPAT" - zakiya humaira; Zaskia Emily Khairunnisa (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2026)
This study aims to analyze the correlation between the intensity of organizational involvement and academic achievement, as well as identify soft skills that develop through "Lecture-Meeting" activities. This study uses a descriptive quantitative approach with a survey design. The research population is S1 students who are registered as active members of internal student organizations (BEM, HIMA, and UKM) for at least one semester. The sample was determined using a purposive sampling technique with a total of 23 students who met the criteria. The results of the study show that student participation in organizations has a positive impact on the development of soft skills, especially in the aspects of leadership, discipline, responsibility, time management, and colaboration. The majority of respondents experienced improvements in various aspects of self-development, and felt more organized in managing academic and non-academic schedules. In academic development, most respondents showed stability in GPA scores. This indicates that organizational activities do not significantly reduce students' academic achievement. Overall, organizational activities contribute positively to the development of discipline. Organizational activities are not a factor in decreasing academic achievement, but are able to support improved performance in managing time and setting priorities. Thus, the organization becomes an effective forum for student academic development.